Evaluation of 4-tert-Butyl-Benzhydrylamine Resin (BUBHAR) as an Alternative Solid Support for Peptide Synthesis - Souza, Sinval E. G.; Malavolta, Luciana; Salomoni, Luiggi F.; Cilli, Eduardo M.; Schreier, Shirley; Jubilut, Guita N.; Nakaie, Clovis R. (Hindawi, 2020)
Following preliminary reports that introduced 4-Tert-butylbenzhydrylamine resin (BUBHAR) as a novel polymer for use in solid-phase peptide chemistry (SPPS), some physical-chemical properties of its structure, certainly relevant for its application in this methodology, were compared with those of the largely used methylbenzhydrylamine resin (MBHAR). In order to rule out possible MBHAR-related commercial source effects for SPPS, we initially compared MBHAR batches acquired from three different manufacturers with homemade BUBHARs. The bead solvation properties of these two resins in solvents used in the tert-butyl (Boc-based) SPPS technique indicated that the mean swelling values of these solid supports (% volume of solvated bead occupied by the solvent) were 51% and 67% for MBHAR and BUBHAR, respectively. This result strongly suggests a good potential for the latter polymer in terms of application for application in SPPS. In order to move forward with this approach, the synthesis of the carboxy-Terminal peptide fragment (Gln-Asn-Cys-Pro-(D-Arg)-Gly-Amide) of the antidiuretic hormone, desmopressin ([3-Mpa∗-Tyr-Phe-Gln-Asn-Cys-Pro-(D-Arg)-Gly-Amide], ∗1-[3-mercaptopropionic acid]), which our laboratory is producing routinely in large scale for the Health Secretary of Sao Paulo State. The comparative synthesis was conducted using these two resins with similar substitution degrees (0.7 mmol/g). In contrast to MBHAR, surprisingly no need for a GlnAsn recoupling reaction was observed when BUBHAR was used. This result might be due to improved solvation of the desmopressin C-Terminal Asn-Cys-Pro-(D-Arg)-Gly-segment when bound to this latter resin as observed by microscopic swelling degrees of peptide-resin beads and also by greater mobility detected of peptide chains within the BUBHAR polymer backbone. This finding was determined by comparative electron paramagnetic resonance (EPR) of both peptide resins attaching the amino acid-Type paramagnetic 2.2.6.6-Tetramethylpiperidine-1-oxyl-4-Amino-4-carboxylic acid (Toac) spin label early introduced by our group.